PENGARUH DISIPLIN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN DI PT. SHEN MAKMUR SENTOSA (J&T EXPRESS) BATURAJA - Rosmala Dewi; Rr.Dimas Veronica Priharti; Sinta Antriani (Ekonomika, 2023)
The Influence of Work Discipline and Work Stress on Employees’ Performance at PT.Shen Makmur Sentosa (J&T Express) Baturaja. This study aimed to find out the influenceof Work Discipline and Work Stress on Employees’ Performance at PT. Shen MakmurSentosa (J&T Express) Baturaja. The data analysis technique used was Multiple LinearRegression. Based on the partial analysis results, there was an influence of workdiscipline on employees’ performance at PT. Shen Makmur Sentosa (J&T Express)Baturaja with a t-count value of 3.525. The work stress variable had an influence onemployees’ performance at PT. Shen Makmur Sentosa (J&T Express) Baturaja with a tcount value of 3.894. Simultaneously, there was an influence of work discipline and workstress on employees’ performance at PT. Shen Makmur Sentosa (J&T Express) Baturaja.The coefficient of determination (R2) obtained was 0.728. This meant that thecontribution of the influence of work discipline and work stress on employees’performance was 72.8% while the remaining 27.2% was influenced by other variablesoutside of this research, such as ability, competence, leadership, and work culture(Afandi, 2021:84)